2001
DOI: 10.1037/0033-2909.127.3.376
|View full text |Cite
|
Sign up to set email alerts
|

The job satisfaction–job performance relationship: A qualitative and quantitative review.

Abstract: A qualitative and quantitative review of the relationship between job satisfaction and job performance is provided. The qualitative review is organized around 7 models that characterize past research on the relationship between job satisfaction and job performance. Although some models have received more support than have others, research has not provided conclusive confirmation or disconfirmation of any model, partly because of a lack of assimilation and integration in the literature. Research devoted to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

117
2,392
14
132

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,294 publications
(2,845 citation statements)
references
References 269 publications
117
2,392
14
132
Order By: Relevance
“…From this result it can be deduced that the perception of PA satisfaction is positively correlated to employee job satisfaction, as the Pearson correlation is significantly large. These results are consistent with previous studies (Bartlett & Kang 2004;Judge, et al 2001;Locke 1970;Schmidt 2007). …”
Section: Insert Table 3 Here -------------------------supporting
confidence: 94%
See 1 more Smart Citation
“…From this result it can be deduced that the perception of PA satisfaction is positively correlated to employee job satisfaction, as the Pearson correlation is significantly large. These results are consistent with previous studies (Bartlett & Kang 2004;Judge, et al 2001;Locke 1970;Schmidt 2007). …”
Section: Insert Table 3 Here -------------------------supporting
confidence: 94%
“…Job satisfaction refers to the employee's pleasurable or positive emotional state as a result of the appraisal of one's job and job experiences (Bartlett & Kang 2004;Judge, Thoresen, Bono & Patton 2001;Schmidt 2007). For the long-term effectiveness of the organisational system employees' satisfactory perceptions towards PAs are important (Longenecker & Nykodym 1996;Roberts 1992).…”
Section: Review Of Literaturementioning
confidence: 99%
“…A mini-industry of validation studies has used panel data to show that what people say today is a strong predictor of what they will do in the future: links have been established between current well-being and future life expectancy, morbidity, productivity, quits, absenteeism, unemployment duration, and marriage duration. At the same time, a flourishing literature in Psychology has examined the links between measures of job -2 -satisfaction or employee engagement, on the one hand, and firm performance on the other (where this latter includes profitability, productivity, turnover and absenteeism): see, for example, the meta-analyses in Harter et al (2002 and and Judge et al (2001). Were individuals' responses purely idiosyncratic, then they could not be compared to each other and none of the above relationships would pertain.…”
Section: Introductionmentioning
confidence: 99%
“…A fairly recent meta-analysis (Judge et al, 2001) found that the relationship between job satisfaction and performance can be moderated by job complexity, such that the correlation between satisfaction and performance is higher for high-complexity jobs (ρ = .52) than for jobs of a low to moderate complexity (ρ = .29). Since MBA students in both China and Norway must be regarded as highly skilled people, one must assume that they relate positively to job complexity.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%